ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI DAN PENDAPATAN PETANI PADI SAWAH DI DESA BANGKIR KECAMATAN DAMPAL SELATAN KABUPATEN TOLITOLI - Supriadi, M. Gafur (Katalogis, 2013)
This research has been implemented in Bangkir village of South Dampal District of Tolitoli Regency, the purpose to know 1) whether the input of land production, man power, seeds, and fertilizer are significance affect towards rice production at Bangkir village of South Dampal District. 2) to know that whether the production input using in the paddy rice land at Bangkir village of South Dampal District have reached efficient rate. 3) to know how big the income of rice paddy farmer in Bangkir Village of South Dampal District if is seen from the production which is obtained into for once weather planted. This research as like a survey an object has been decided with the target for 41 rice farmers in Bangkir Village of South Dampal District. To see the influence from each factors which is examined that’s used Cobb-Douglas analysis model which is made a transformation into multiple linear regression forms. The conclusion from this research either simultaneous or variable partial of land wide, man power, fertilizer and seed affect to the rice production in Bangkir Village. The input using of production indicate that the land is not efficiently, so that still probably increase the production input, but production input, man power, fertilizer and seeds are not efficiently.